The Influence of Return On Asset, Debt to Equity Ratio and Earning Per Share on Stock Price PT Hanjaya Mandala Sampoerna Tbk Period 2010-2023 - Novelia, Airin (Yayasan Pendidikan Penelitian Pengabdian Al-amsi, 2024)
This research aims to determine the effect of Return On Asset, Debt to Equity Ratio and Earning Per Share on Stock Price. The independent variables are Return On Asset, Debt to Equity Ratio and Earning Per Share and the dependent variable is Stock Price. Using quantitative research methods, the sample and population used in this study are the annual financial statements of PT Hanjaya Mandala Sampoerna Tbk for the period 2010-2023 The results showed that partially Return On Asset had no effect and was not significant to the Stock Price. Debt to Equity Ratio partially and significantly affects the Price and Earning Per Share partially has no effect and is not significant to the Share Price. Then the f test shows that simultaneously Return On Asset, Debt to Equity Ratio and Earning Per Share have a significant effect on Stock Price.